Գրիգոր Լուսավորչի «Ճառք յաճախապատումք» երկը - Ն. Լ. Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
“Многовещательные речи” Григория Просветителя–это одна из самых важных работ литургического характера в армянской религиозной литературе. Труд Григория Просветителя имеет огромное морально-дидактическое значение. The “Faithful Speeches” of Gregory the Illuminator is one of the most important works of the liturgical character in the Armenian religious literature. The work of Gregory the Illuminator has a great moral-didactic significance.
Keywords: Literature; B Philosophy; Psychology; Religion; Language and Literature; BL Religion; BT Doctrinal Theology